UCh MEZONLI DETERMINISTIK ChIZIQLI DASTURLASh MASALASI UChUN DASTURIY MAJMUA IShLAB ChIQISh - Uteuliev, N.U.; Orinbaev, A.B.; Madreymova, Z.B. (SCIENCE and SOCIETY, 2025)
This article is devoted to developing a software package for a three-objective linear programming problem in agriculture based on the cost-profit-water criteria and to evaluating it through computational experiments. The obtained solutions were evaluated using Pareto analysis.